OCCURRENCE OF NATURAL FULLERENES IN LOW GRADE METAMORPHOSED PROTEROZOIC SHUNGITE FROM KARELIA, RUSSIA - Parthasarathy G.; Srinivasan R.; Vairamani M.; Ravikumar K.; Kunwar A.C. (My University, 1998)
We report on the occurrence of fullerenes in Proterozoic shungite (∼2 Ga) from the shungite mine, Kondopoga, Karelia, Russia (62.12°N 34.17°E). The presence of fullerenes has been confirmed by mass spectrometry, with peaks at 360 and 720 amu (atomic mass unit), powder X-ray diffraction showing ten diffraction peaks corresponding to the fullerite structure with a = 1.4201(5) nm, and 13C nuclear magnetic resonance (NMR) spectroscopic studies, showing a peak at 143.2 ppm. In the Kondopoga shungite mine, fullerenes occur in silty shales that have experienced greenshist facies metamorphism.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой